Particle-carrying fiber structure and method for producing same
Patent Information
- Application Number
- JP2021040905
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-14
- Filing Date
- 2021-03-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-03-15
AI Technical Summary
【0011】 本発明の粒子担持繊維構造体は、カルボキシル基を有しながら、低い収縮率を達成でき、これまで担持量を多くすることが困難であった機能性粒子も脱落を抑制しつつ、従来よりも多量に担持することができる。このため、本発明の粒子担持繊維構造体は、機能性粒子の機能性を活用する機能性フィルター、燃料電池拡散膜用カーボンシート、摩擦材、機能性製紙製品、意匠紙、透湿紙、電池部材などの機能性材料として好適に使用することができる。
Smart Images

Figure 0007641481000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a particle-carrying fiber structure containing beaten acrylonitrile fibers, functional particles and a cationic compound, and a method for producing the same. [Background technology]
[0002] Beaten fibers are characterized by their hyperbranched structure and high specific surface area, and are excellent in adhesiveness and in capturing functional particles such as activated carbon. As a result, they are used in a wide range of fields, including papermaking, packaging materials, paints, building materials, industrial materials, beauty, and health.
[0003] It has been considered to beat acrylonitrile fibers as well, and Patent Documents 1 and 2 report that beaten acrylonitrile fibers having high adhesiveness can be obtained by beating acrylonitrile fibers having carboxyl groups.
[0004] These beaten acrylonitrile fibers have the adhesive properties and ability to capture functional particles as described above, and because they contain carboxyl groups, they exhibit functions such as easy dispersion, ion adsorption, moisture absorption, and deodorization, and are expected to be used in a variety of applications. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-166118 A [Patent Document 2] Patent No. 6656608 Summary of the Invention [Problem to be solved by the invention]
[0006] The beaten acrylonitrile fiber of Patent Document 1 has a property of high swelling in water, and is considered to be advantageous in terms of powder capture. However, this property also creates an aspect that it is easy to shrink when heated or dried, causing a problem of poor shape stability during processing. In addition, the beaten acrylonitrile fiber of Patent Document 1 has a property that once the fibrillated fiber is dried, the fibrils adhere to each other and do not swell again. Therefore, there is also a problem that once it is dried, the properties of the carboxyl group, such as ion adsorption, moisture absorption, and deodorization, cannot be effectively utilized.
[0007] In addition, the beaten acrylonitrile fiber of Patent Document 2 overcomes the above problems and has excellent particle capture properties, but has problems with supporting functional particles having a negative surface charge, such as zeolite having adsorptive properties, silicon having lithium ion occlusion properties, and organic fine particles having moisture absorbing and releasing properties, in that the amount of functional particles supported cannot be increased and they tend to fall off.
[0008] The present invention was devised in consideration of the current state of the prior art, and its object is to provide a particle-supported fiber structure that has excellent shape stability and an excellent amount of functional particles supported, and a method for producing the same. [Means for solving the problem]
[0009] As a result of intensive research conducted by the inventors in order to achieve the above-mentioned object, it was discovered that by using beaten acrylonitrile-based fibers having a carboxyl group content of 0.2 to 4.0 mmol / g and composed of a polymer substantially free of a crosslinked structure formed by a covalent bond in combination with a cationic compound, a particle-loaded fiber structure having excellent dimensional stability and an excellent amount of functional particles loaded thereon can be obtained, thereby arriving at the present invention.
[0010] That is, the present invention is achieved by the following means. (1) A polymer having a carboxyl group content of 0.2 to 4.0 mmol / g and substantially no crosslinked structure due to a covalent bond. and grammage 50g / m2 When the paper is shaped like this, it exhibits a shrinkage rate of 20% or less. Beaten acrylonitrile fibers, Has a negative charge A particle-carrying fiber structure comprising functional particles and a cationic compound. (2) A particle-supporting fiber structure according to (1), characterized in that the total amount of the functional particles and the cationic compound supported is 1.0 g / g or more based on the weight of the beaten acrylonitrile fibers. (3) The particle-supporting fiber structure according to (1) or (2), wherein the amount of the cationic compound added is 0.01 to 5.0% by weight based on the weight of the functional particles. ( 4 The functional particles are hygroscopic particles (1) to ( 3 ) The particle-supporting fiber structure according to any one of the preceding claims. ( 5 The cationic compound is a polymer having a weight average molecular weight of 5,000 or more. 4 ) The particle-supporting fiber structure according to any one of the preceding claims. ( 6 ) (1) ~ ( 5 2. A filter, a carbon sheet for a fuel cell diffusion membrane, a friction material, a functional paper product, a decorative paper, a moisture-permeable paper or a battery component, comprising the particle-supporting fiber structure according to any one of claims 1 to 11. ( 7 ) Has a negative charge After the functional particles are combined with a cationic compound, the resulting composite is composed of a polymer having a carboxyl group amount of 0.2 to 4.0 mmol / g and substantially no crosslinked structure due to a covalent bond. and grammage 50g / m 2 When the paper is shaped like this, it exhibits a shrinkage rate of 20% or less. A method for producing a particle-supported fiber structure, comprising supporting particles on beaten acrylonitrile fibers. Effect of the Invention
[0011] The particle-supported fiber structure of the present invention can achieve a low shrinkage rate while having carboxyl groups, and can support a larger amount of functional particles than before, which has been difficult to support in large amounts until now, while suppressing the falling off of the functional particles. Therefore, the particle-supported fiber structure of the present invention can be suitably used as a functional material such as a functional filter that utilizes the functionality of the functional particles, a carbon sheet for a fuel cell diffusion membrane, a friction material, a functional paper product, a decorative paper, a moisture-permeable paper, and a battery component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The beaten acrylonitrile fiber used in the present invention contains carboxyl groups, and the content thereof is 0.2 to 4.0 mmol / g, preferably 0.4 to 3.0 mmol / g, and more preferably 0.6 to 2.0 mmol / g, as described below. If the amount of carboxyl groups is less than 0.2 mmol / g, the adhesiveness, particle capture performance, etc. may not be sufficient, and if it exceeds 4.0 mmol / g, the hydrophilicity of the fiber becomes too high, and the fiber swells or dissolves in water, which adversely affects the fiber properties. In addition, in order to obtain good beatability in the acrylonitrile fiber before beating (hereinafter also referred to as unbeaten fiber) which is the raw material of the beaten acrylonitrile fiber used in the present invention, it is desirable to contain carboxyl groups in the range shown above.
[0013] In addition, in the above unbeaten fibers, if a crosslinked structure due to a covalent bond is present, each polymer constituting the fiber is linked and the beating property is reduced, so one that does not substantially have a crosslinked structure due to a covalent bond is adopted. As a result, the beaten acrylonitrile-based fiber adopted in the present invention also has substantially no crosslinked structure due to a covalent bond. Here, "substantially no crosslinked structure due to a covalent bond" means that it does not have a crosslinked structure intentionally formed by using a crosslinking agent or the like, and does not mean that it does not have even a trace amount of crosslinked structure that may be unintentionally by-produced in the hydrolysis treatment described later.
[0014] The beaten acrylonitrile fiber used in the present invention has a basis weight of 50 g / m 2 It is desirable that the shrinkage rate of the paper is less than 25%, preferably 20% or less, and more preferably 15% or less when the paper is shaped like this. If the shrinkage rate exceeds 25%, problems may occur in terms of shape stability during processing or actual use.
[0015] The beaten acrylonitrile fiber used in the present invention has a water swelling degree (also simply referred to as "water swelling degree" in the present invention) after drying from the wet state after beating is preferably 0.2 times or more, more preferably 0.4 times or more, even more preferably 0.7 times or more, and most preferably 1 times or more. If the water swelling degree is less than 0.2 times, the spread of the fibrils may be weak and the particle carrying capacity may be low. On the other hand, if the water swelling degree is too high, the fiber may become embrittled and powdered due to swelling, so the upper limit is preferably 10 times, more preferably 8 times.
[0016] The beaten acrylonitrile fibers employed in the present invention desirably have a freeness of 730 ml or less. If the freeness exceeds 730 ml, the particle capturing ability may not be significantly exhibited.
[0017] In addition, in the internal structure of the unbeaten fiber, it is desirable that the portion having a carboxyl group is present throughout the fiber structure made of an acrylonitrile polymer, but is not uniformly mixed at the molecular level. Specific examples of such structures include small fibers (so-called fibrils) constituting the acrylonitrile fiber that have a core-sheath structure with a carboxyl group on the surface layer and no carboxyl group in the center, that is, a structure consisting of an aggregate of small fibers having a core-sheath structure with a carboxyl group in the sheath portion. Here, "present throughout the fiber" means that the coefficient of variation CV of the magnesium element content in the fiber cross section measured by the measurement method described below is 50% or less. The coefficient of variation CV is preferably 40% or less, more preferably 30% or less.
[0018] If the carboxyl groups are unevenly distributed in the fiber structure or uniformly distributed at the molecular level, sufficient beating properties may not be obtained. In a structure in which the parts having carboxyl groups are distributed throughout the fiber and are not uniformly mixed at the molecular level, the parts having carboxyl groups swell in water and become easily torn, which facilitates fibrillation by beating.
[0019] Furthermore, the surface of each beaten fibril becomes rich in carboxyl groups, which increases hydrophilicity and water diffusibility, and also makes it easier to exhibit particle capture properties, adhesive properties, etc. On the other hand, the inside of each fibril is composed of an acrylonitrile polymer, which makes it difficult to shrink and contributes to shape stability.
[0020] In order to further improve the beating properties of the unbeaten fibers, it is preferable that the counter ions of the carboxyl groups are cations other than hydrogen ions. More specifically, it is desirable that the proportion of counter ions that are cations other than hydrogen ions, i.e., the degree of neutralization, is preferably 25% or more, more preferably 35% or more, and even more preferably 50% or more.
[0021] Examples of the cations include alkali metals such as Li, Na, and K, alkaline earth metals such as Mg, Ca, and Ba, metals such as Cu, Zn, Al, Mn, Ag, Fe, Co, and Ni, and cations such as NH4 and amines. A mixture of multiple types of cations is also acceptable. Among them, Li, Na, K, Mg, Ca, and Zn are preferred.
[0022] The above-mentioned method for producing the beaten acrylonitrile-based fiber used in the present invention includes a method in which a spinning dope in which an acrylonitrile-based polymer is dissolved is spun from a nozzle, and the undried fiber obtained through each step of coagulation, washing with water, and drawing is hydrolyzed to produce an unbeaten fiber, and the unbeaten fiber is beaten. The production method will be described in detail below.
[0023] First, the acrylonitrile polymer used as the raw material contains acrylonitrile in a polymerization composition of preferably 40% by weight or more, more preferably 50% by weight or more, and even more preferably 85% by weight or more. Therefore, as the acrylonitrile polymer, in addition to acrylonitrile homopolymers, copolymers of acrylonitrile and other monomers can also be used. The other monomers in the copolymer are not particularly limited, but include vinyl halide and vinylidene halide; (meth)acrylic acid esters (note that the notation (meth) refers to both those with and without the word meta); sulfonic acid group-containing monomers such as methallylsulfonic acid and p-styrenesulfonic acid and their salts, acrylamide, styrene, vinyl acetate, etc.
[0024] Next, the acrylonitrile polymer is used to form fibers by wet spinning. The following description will be given of the case where an inorganic salt such as sodium rhodanate is used as the solvent. First, the acrylonitrile polymer is dissolved in a solvent to prepare a spinning dope. After the spinning dope is spun from a nozzle, it is subjected to the steps of coagulation, water washing, and stretching, so that the moisture content of the undried fiber (hereinafter also referred to as gelled acrylonitrile fiber) is 20 to 250% by weight, preferably 25 to 130% by weight, and more preferably 30 to 100% by weight.
[0025] Here, if the moisture content of the gelled acrylonitrile fiber is less than 20% by weight, the agent may not penetrate into the fiber in the hydrolysis treatment described below, and carboxyl groups may not be generated throughout the fiber. If the moisture content exceeds 250% by weight, the fiber contains a lot of moisture inside, and the fiber strength becomes too low, which is not preferable because it reduces spinnability. If high fiber strength is more important, it is preferable to set the moisture content within the range of 25 to 130% by weight. There are many methods for controlling the moisture content of the gelled acrylonitrile fiber within the above range, and for example, the coagulation bath temperature is -3°C to 15°C, preferably -3°C to 10°C, and the stretch ratio is 5 to 20, preferably 7 to 15 times.
[0026] The gelled acrylonitrile fibre is then subjected to a hydrolysis treatment, by which the nitrile groups in the gelled acrylonitrile fibre are hydrolyzed to produce carboxyl groups.
[0027] Examples of such hydrolysis treatment methods include a method of impregnating or immersing the fiber in a basic aqueous solution such as an alkali metal hydroxide, an alkali metal carbonate, or ammonia, or an aqueous solution such as nitric acid, sulfuric acid, or hydrochloric acid, and then subjecting the fiber to heat treatment. As specific treatment conditions, various conditions such as the concentration of the treatment agent, reaction temperature, and reaction time may be appropriately set in consideration of the range of the amount of carboxyl groups described above. In general, it is preferable to set the conditions within the range of 0.5 to 20% by weight, preferably 1.0 to 15% by weight, impregnated with the treatment agent, squeezed, and then treated in a moist heat atmosphere at a temperature of 105 to 140°C, preferably 110 to 135°C, for 10 to 60 minutes, from the viewpoints of industry and fiber physical properties. In addition, if the temperature is less than 105°C, the fiber may become strongly colored. The moist heat atmosphere refers to an atmosphere filled with saturated steam or superheated steam.
[0028] In the fibers subjected to the hydrolysis treatment as described above, salt-type carboxyl groups are generated with cations such as alkali metals and ammonium as counter ions according to the types of alkali metal hydroxides, alkali metal carbonates, ammonia, etc. used in the hydrolysis treatment, and subsequently, a treatment for changing the counter ions of the carboxyl groups may be carried out as necessary. By carrying out an ion exchange treatment with an aqueous solution of a metal salt such as a nitrate, sulfate, or hydrochloride, it is possible to obtain salt-type carboxyl groups with a desired metal ion as the counter ion. Furthermore, by adjusting the pH of the aqueous solution or the concentration and type of the metal salt, it is possible to mix different types of counter ions and adjust their ratio.
[0029] The fibers into which carboxyl groups have been introduced as described above, i.e., unbeaten fibers, are washed with water, dried, cut, and then subjected to a beating treatment, as necessary. The beating method is not limited, and a beating machine such as a beater or a refiner can be used.
[0030] The beaten acrylonitrile fiber used in the present invention is obtained in the above manner, but the production of the unbeaten fiber can be carried out continuously by utilizing existing continuous production facilities for acrylic fiber. In the above-mentioned method, an inorganic salt such as sodium rhodanate is used as a solvent, but the above conditions are the same even when an organic solvent is used. However, since the type of solvent is different, the coagulation bath temperature is selected to be suitable for the solvent, and the moisture content of the gelled acrylonitrile fiber is controlled within the above range.
[0031] In addition, in the above-mentioned manufacturing method, since the gel-like acrylonitrile fiber having a void structure is hydrolyzed, it is considered that the hydrolysis does not proceed sequentially from the fiber surface, but the chemical penetrates into the inner part of the fiber through the voids, and hydrolysis occurs throughout the entire fiber. Furthermore, from a microscopic perspective, since acrylonitrile fibers generally exist as a collection of fine fibrils, it is expected that the chemical penetrates between the fibrils, hydrolysis proceeds from the fibril surface, and the original acrylonitrile polymer remains inside the fibrils without being hydrolyzed. That is, a structure is formed in which the parts having carboxyl groups exist throughout the fiber, and are not uniformly mixed at the molecular level, and fibrillation is facilitated with the parts having carboxyl groups as boundaries. It is also assumed that after beating, the particle capture ability is improved by the carboxyl groups on the surface of each fibril, and the acrylonitrile polymer remaining inside exhibits low heat shrinkage.
[0032] In the above-mentioned manufacturing method, when the gel-like acrylonitrile fiber, i.e., the undried fiber after drawing is not used, and the dried acrylonitrile fiber is subjected to hydrolysis treatment, the chemical does not penetrate deep inside the fiber, and hydrolysis is carried out successively from the surface of the fiber, leading to a structure in which the surface layer of the fiber has many carboxyl groups and the deep inside of the fiber has few carboxyl groups. In such a structure, the beating property is significantly deteriorated.
[0033] The particle-supported fiber structure of the present invention may contain fibers other than the above-mentioned beaten acrylonitrile-based fibers. Examples of such fibers include acrylic fibers, aramid fibers, staples and short fibers such as cotton, rayon, polyethylene, polypropylene, and polyester, and pulp-like fibers such as cellulose pulp, acrylic pulp, and aramid pulp, and a plurality of types may be used. The content of the beaten acrylonitrile-based fibers is preferably 1 to 100% by weight, more preferably 5 to 100% by weight, based on the total weight of the particle-supported fiber structure excluding the functional particles and the cationic compound. If the content of the beaten acrylonitrile-based fibers is less than 1% by weight, the amount of particles that can be supported in the particle-supported fiber structure is reduced, and the functionality is reduced, which is not preferable.
[0034] Next, examples of functional particles that can be used in the present invention include zeolite, silicon, iron oxide, carbon black, silica gel, and organic moisture absorbing and releasing particles, and zeolite, silica gel, and organic moisture absorbing and releasing particles, which are hygroscopic particles, are particularly suitable. These generally have a negative charge. On the other hand, the beaten acrylonitrile fibers used in the present invention also have a negative charge because they have a carboxyl group. Therefore, even if these are simply mixed, it is difficult to increase the amount of support due to electronic repulsion. Therefore, in the present invention, by combining a cationic compound described later, it is possible to support a large amount of functional particles that have a negative charge. The charge mentioned here refers to the surface charge, and can generally be measured as a zeta potential.
[0035] The total loading amount of functional particles and cationic compound in the particle-supported fiber structure of the present invention (hereinafter also simply referred to as "particle loading amount") is preferably 1.0 g / g or more, more preferably 2.0 g / g or more, and even more preferably 3.0 g / g or more, based on the weight of the beaten acrylonitrile fiber described above. If the particle loading amount is less than 1.0 g / g, the amount of particles in the particle-supported fiber structure will be small, resulting in low functionality, which is not preferred. On the other hand, if the particle loading amount is too high, the particles will be more likely to fall off, so it is desirable to keep it below 100 g / g.
[0036] The average particle size of the functional particles used in the present invention is not particularly limited, but is preferably 1 nm to 100 μm, more preferably 50 nm to 75 μm, and even more preferably 100 nm to 50 μm. If the average particle size is less than 1 nm or more than 100 μm, the particle supportability may deteriorate, which is undesirable.
[0037] The cationic compound used in the present invention suppresses the electrostatic repulsion between the beaten acrylonitrile fibers and the functional particles having a negative charge, and plays a role as a binder that supports the functional particles on the beaten acrylonitrile fibers. That is, it is considered that the negative charge of the functional particles is cancelled by being combined with the cationic compound, and the combined cationic compound is bonded to the carboxyl group of the beaten acrylonitrile fibers. Such cationic compounds are not particularly limited as long as they can cancel the negative charge of the functional particles, and examples thereof include quaternary ammonium compounds and amino group-containing polymers. More specifically, tetrabutylammonium bromide, polyallylamine, polyethyleneimine, N-dimethylaminoethyl methacrylic acid copolymer, diallyldimethylammonium chloride copolymer, diallylamine salt copolymer, etc. are included.
[0038] The amount of cationic compound added varies depending on the properties of the functional particles to be supported, but it is often effective to improve the amount of support by preferably 0.01 to 5.0% by weight, more preferably 0.02 to 2.5% by weight, and even more preferably 0.02 to 1.5% by weight based on the weight of the functional particles. If the amount added is too small, the negative charge of the functional particles may remain, and the effect of improving the amount of support may not be sufficiently obtained. On the other hand, if the amount added of the cationic compound is too large, the carboxyl group of the beaten acrylonitrile fiber may be blocked by the excess cationic compound, and electron repulsion may occur between the cationic compound and the functional particles composited therewith, resulting in a decrease in the amount of support.
[0039] When such a cationic compound is a polymer, the molecular weight thereof depends on the type of polymer used, but in many cases, the effect of improving the particle carrying amount is easily obtained when a weight average molecular weight of preferably 5000 or more, more preferably 10000 or more, and even more preferably 15000 or more is used. On the other hand, the upper limit of the weight average molecular weight is not particularly limited, but since the viscosity increases and handling becomes more difficult as the molecular weight increases, it is generally desirable that the weight average molecular weight is 100000 or less.
[0040] The form of the particle-supported fiber structure of the present invention described above can be, for example, paper, nonwoven fabric, woven fabric, knitted fabric, a molded product obtained by laminating these, a rolled cylindrical molded product, etc. A method for producing such a particle-supported fiber structure of the present invention is preferably carried out by first compounding functional particles with a cationic compound, and then supporting the compound on beaten acrylonitrile fibers.
[0041] For example, when the particle-supported fiber structure of the present invention is paper, a manufacturing method can be a method in which a cationic compound is added to a functional particle dispersion liquid to combine the functional particles with the cationic compound, and then beaten acrylonitrile-based fibers are added and the paper is manufactured by a conventional wet papermaking method.
[0042] The particle-supported fiber structure of the present invention described above can be used alone or in combination with other materials in many applications. Examples of such applications include diffusion layers and absorption layers of hygiene products such as diapers, urine absorption pads, and sanitary napkins, activated carbon-supported sheets, filters such as water purification filters, deodorizing filters, and filtration filters, carbon sheets for fuel cell diffusion membranes, battery components such as separators and electrode reinforcements, friction materials such as clutch facings and brake pads, functional paper products such as deodorizing wallpaper, moisture-absorbing wallpaper, moisture-permeable paper, and latent heat exchange sheets, and decorative paper such as fancy paper. In addition, when combined with other materials, it is desirable to set the content of the particle-supported fiber structure of the present invention to preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 20% by weight or more, from the viewpoint of expressing the functionality of the particle-supported fiber structure of the present invention. EXAMPLES
[0043] Examples are shown below to facilitate understanding of the present invention, but these are merely illustrative and the gist of the present invention is not limited thereto. In the examples, parts and percentages are by weight unless otherwise specified. In addition, each property was measured by the following method.
[0044] <Carboxyl group distribution within the fiber structure> An unbeaten fiber sample is immersed in an aqueous solution of magnesium nitrate equivalent to twice the amount of carboxyl groups contained in the fiber at 50°C for 1 hour to carry out ion exchange treatment, and then washed with water and dried to convert the counter ion of the carboxyl groups to magnesium. For the fiber sample in the magnesium salt form, an energy dispersive X-ray spectrometer (EDS) is used to measure the magnesium element content at 10 measurement points selected at approximately equal intervals from the outer edge to the center of the fiber cross section. The coefficient of variation CV [%] is calculated from the values obtained for each measurement point using the following formula. Coefficient of variation CV [%] = (standard deviation / average value) x 100
[0045] <Amount of carboxyl groups> Approximately 1 g of the beaten sample is weighed out and soaked in 50 ml of 1 mol / l hydrochloric acid for 30 minutes, then washed and soaked in pure water with a bath ratio of 1:500 for 15 minutes. After washing with water until the bath pH is 4 or higher, it is dried in a hot air dryer at 105°C for 5 hours. Approximately 0.2 g of the dried sample is precisely weighed out (W1 [g]), and 100 ml of water, 15 ml of 0.1 mol / l sodium hydroxide, and 0.4 g of sodium chloride are added and stirred. Next, the sample is filtered using a wire mesh and washed with water. Two to three drops of phenolphthalein solution are added to the obtained filtrate (including the washing liquid), and titration is performed using 0.1 mol / l hydrochloric acid according to the usual method to determine the amount of hydrochloric acid consumed (V1 [ml]), and the total amount of carboxyl groups is calculated using the following formula. Total amount of carboxyl groups [mmol / g] = (0.1 × 15 - 0.1 × V1) / W1
[0046] <Neutralization level> The beaten sample is dried in a hot air dryer at 105°C for 5 hours, and approximately 0.2 g is weighed out (W2 [g]). 100 ml of water, 15 ml of 0.1 mol / l sodium hydroxide, and 0.4 g of sodium chloride are added and stirred. The sample is then filtered through a wire mesh and washed with water. 2 to 3 drops of phenolphthalein solution are added to the obtained filtrate (including the washings), and titration is performed with 0.1 mol / l hydrochloric acid in the usual manner to determine the amount of hydrochloric acid consumed (V2 [ml]). The amount of H-type carboxyl groups contained in the sample is calculated using the following formula, and the degree of neutralization is calculated from this result and the total amount of carboxyl groups mentioned above. H-type carboxyl group amount [mmol / g] = (0.1 × 15 - 0.1 × V2) / W2 Degree of neutralization [%] = [(total amount of carboxyl groups - amount of H-type carboxyl groups) / total amount of carboxyl groups] x 100
[0047] <Freeness (CSF)> JIS P 8121-2:2012 Pulp-Test method for freeness-Part 2: Measured according to the Canadian standard freeness method.
[0048] <Shrinkage rate> The beaten sample was made into a water slurry and spun into a sheet with a basis weight of 50 g / m using a square sheet machine manufactured by Kumagai Riki Kogyo Co., Ltd. 2The paper is then cut into a size of 25cm x 25cm. It is then dried at 105℃ for 1 hour, and the lengths of each of the four sides are measured. The average length of one side (B [cm]) is calculated from the measurements, and the shrinkage rate is calculated using the following formula. Shrinkage rate (%) = (25-B) / 25×100
[0049] <Water swelling degree> The beaten sample was made into a water slurry and spun into a sheet with a basis weight of 50 g / m using a square sheet machine manufactured by Kumagai Riki Kogyo Co., Ltd. 2 The paper is made so that the weight of the paper is 105°C and dried for 1 hour to prepare paper for evaluation, and its weight (W3 [g]) is measured. The paper for evaluation is then immersed in pure water and centrifuged for 5 minutes at 1200 rpm. The weight after dehydration (W4 [g]) is measured, and the degree of water swelling is calculated using the following formula. Water swelling ratio [times] = (W4-W3) / W3 The centrifugal dehydration is performed using a KUBOTA centrifugal dehydrator (KS-8000) and a universal swing rotor (RS3000 / 6) equipped with a stainless steel basket.
[0050] <Moisture content of gel-like acrylonitrile fiber> The gelled acrylonitrile fiber is immersed in pure water and then dehydrated for 2 minutes in a centrifugal dehydrator (TYPE H-770A manufactured by Kokusan Centrifugal Machinery Co., Ltd.) at a centrifugal acceleration of 1100G (G indicates the acceleration of gravity). After the dehydration, the weight is measured (referred to as W5 [g]), and the undried fiber is dried at 120°C for 15 minutes, and the weight is measured (referred to as W6 [g]) and calculated according to the following formula. Moisture content of gelled acrylonitrile fiber (%) = (W5-W6) / W5 x 100
[0051] <Method for measuring zeta potential of particles> The sample in the water suspension adjusted to pH = 10.0 was measured using an Otsuka Electronics ELSZ.
[0052] <Preparation of particle-supported fiber structures and measurement of particle support amount> A cationic compound (allylamine polymer: PAA-15C (weight average molecular weight 15,000), PAA-05 (weight average molecular weight 5,000), PAA-25 (weight average molecular weight 25,000) manufactured by Nittobo Medical Co., Ltd., diallyldimethylammonium chloride polymer: PAS-H-5L (weight average molecular weight 30,000) manufactured by Nittobo Medical Co., Ltd., or TBAB (tetrabutylammonium bromide)) was added in an amount (weight % based on the functional particles) shown in Table 1 to 1 L of pure water, and functional particles (zeolite (synthetic zeolite manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added. Add 12.0 g of zeolite: F-9 (passed through 200 mesh, zeta potential: -1.8 mV), organic moisture absorptive and desorbing particles (moisture absorptive and desorbing fine particles Tuftic (registered trademark) HU-750P (average particle size 50 μm, zeta potential: -28.5 mV) manufactured by Nippon Exlan Industrial Co., Ltd.), or silicon (Sigma-Aldrich silicon: product number 215619 (passed through 325 mesh, zeta potential: -39.2 mV)) and stir for 10 minutes. Then, add 1.0 g of sample fiber equivalent to the dry weight and stir for 30 minutes. Then, pass the mixture through a sieve with 173 μm mesh (area 200 cm). 2 The residue on the sieve was dried at 105°C for 5 hours to prepare a particle-supported fiber structure. The weight (A [g]) of the obtained particle-supported fiber structure was measured, and the amount of particles supported per 1 g of sample fiber was calculated using the following formula. Particle loading (g / g) = (A-1.0) / 1.0
[0053] <Water resistance evaluation> The particle-supported fiber structure (W7 [g]) obtained in the above <Preparation of particle-supported fiber structure and measurement of particle support amount> is immersed in a 35°C water bath for 10 minutes, after which the dry weight (W8 [g]) is measured, and the weight loss rate is calculated using the following formula. Weight reduction rate (%) = {(W7-W8) / W7}×100
[0054] <Example 1> A spinning dope in which 10 parts of an acrylonitrile-based polymer consisting of 90% acrylonitrile and 10% methyl acrylate was dissolved in 90 parts of a 44% aqueous sodium thiocyanate solution was spun into a coagulation bath at -2.5°C, coagulated, washed with water, and stretched 12 times to obtain a gel-like acrylonitrile-based fiber with a moisture content of 35%. The fiber was immersed in a 1.5% aqueous sodium hydroxide solution, squeezed, and then hydrolyzed in a moist heat atmosphere at 123°C for 25 minutes, washed with water, and dried at 105°C for 1 hour to obtain an unbeaten fiber. The unbeaten fiber was cut to 4 mm and made into a water slurry with a concentration of 1%, and then beaten with a Niagara beater (BE-23 manufactured by Kumagai Riki Kogyo) with a weight of 2 kg for the beating time listed in Table 1 to obtain a beaten acrylonitrile-based fiber to be used in Example 1. The evaluation results of the fiber and the fiber structure prepared by the above-mentioned method using the fiber are shown in Table 1.
[0055] <Examples 2 to 5 and 10 to 20> Beaten acrylonitrile fibers for Examples 2 to 5 and 10 to 20 were obtained in the same manner as in Example 1, except that the concentration of the aqueous sodium hydroxide solution was changed to 4.0% and the beating treatment was performed for the beating time shown in Table 1. The evaluation results of these fibers and the fiber structures prepared by the above-mentioned method using these fibers are shown in Table 1. In addition, in Examples 5 and 11, the water resistance of the fiber structures obtained using Tuftic HU was evaluated, and the weight loss rates were 0.3% and 0.1%, respectively, indicating excellent water resistance.
[0056] <Examples 6 to 8> In the recipe of Example 1, the concentration of the sodium hydroxide aqueous solution was changed to 7.5% in Example 6, 10.0% in Example 7, and 20.0% in Example 8, and the beating treatment was performed for the beating time shown in Table 1, and the same procedure was followed to obtain beaten acrylonitrile fibers to be used in Examples 6 to 8. The evaluation results of these fibers and the fiber structures prepared by the above-mentioned method using these fibers are shown in Table 1.
[0057] <Example 9> The beaten acrylonitrile fiber for Example 9 was obtained in the same manner as in Example 5, except that a step of adjusting the pH to 3.5 with nitric acid in pure water and maintaining at 60° C. for 30 minutes was inserted between the hydrolysis treatment step and the water washing step. The evaluation results of the fiber and the fiber structure prepared by the above-mentioned method using the fiber are shown in Table 1.
[0058] <Comparative Example 1> The experiment was carried out in the same manner as in Example 11, except that the fiber structure was produced without adding a cationic compound. The evaluation results are shown in Table 1.
[0059] <Comparative Examples 2 and 3> A spinning dope prepared by dissolving 10 parts of an acrylonitrile-based polymer consisting of 95% acrylonitrile, 2% methacrylic acid, and 3% methyl acrylate in 90 parts of a 44% aqueous sodium thiocyanate solution was spun in a conventional manner, coagulated, washed with water, stretched, and then cut to a length of 4 mm without drying, and subjected to a beating treatment in the same manner as in Example 1 to obtain fibers to be used in Comparative Examples 2 and 3. The evaluation results of these fibers and the fiber structures prepared using these fibers by the above-mentioned method are shown in Table 1.
[0060] [Table 1]
[0061] As shown in Table 1, in Examples 1 to 8 and 10 to 20, the unbeaten fibers have good beating properties, and the obtained beaten acrylonitrile fibers have low shrinkage, excellent shape stability, and high particle loading. Note that Example 9, which has a lower degree of neutralization than Example 5, resulted in a lower freeness, indicating that a higher degree of neutralization results in better beating properties.
[0062] On the other hand, the fiber structure of Comparative Example 1, in which no cationic compound was added, had a low particle carrying amount.
[0063] In Comparative Examples 2 and 3, in which acrylonitrile fibers were prepared from polymers obtained by copolymerizing monomers containing carboxyl groups, the shrinkage rate was high and there was a problem with dimensional stability. Furthermore, when the Comparative Example 2 is compared with Example 1, which has the same freeness, it is found that Example 1 of the present invention has a better particle carrying amount. This is considered to be because, in the acrylonitrile fibers of Comparative Examples 2 and 3, carboxyl groups are uniformly present at the molecular level throughout the fibrils, whereas in the beaten acrylonitrile fiber of Example 1, carboxyl groups are localized on the surface of the fibrils.
Claims
1. A particle-supported fiber structure comprising beaten acrylonitrile-based fibers having a carboxyl group content of 0.2 to 4.0 mmol / g, composed of a polymer that is substantially free of a crosslinked structure formed by a covalent bond, and that exhibits a shrinkage rate of 20% or less when formed into a paper form having a basis weight of 50 g / m 2 , functional particles having a negative charge, and a cationic compound.
2. 2. The particle-supporting fiber structure according to claim 1, wherein the total amount of the functional particles and the cationic compound supported is 1.0 g / g or more based on the weight of the beaten acrylonitrile fibers.
3. 3. The particle-carrying fiber structure according to claim 1, wherein the amount of the cationic compound added is 0.01 to 5.0% by weight based on the weight of the functional particles.
4. 4. The particle-carrying fiber structure according to claim 1, wherein the functional particles are hygroscopic particles.
5. 5. The particle-supporting fiber structure according to claim 1, wherein the cationic compound is a polymer having a weight-average molecular weight of 5,000 or more.
6. A filter, a carbon sheet for a fuel cell diffusion membrane, a friction material, a functional paper product, a decorative paper, a moisture-permeable paper, or a battery component, comprising the particle-supporting fiber structure according to any one of claims 1 to 5.
7. A method for producing a particle-supported fiber structure, comprising: compounding negatively charged functional particles with a cationic compound; and then supporting the particles on beaten acrylonitrile-based fibers, which have a carboxyl group content of 0.2 to 4.0 mmol / g, are composed of a polymer that is substantially free of a cross-linked structure formed by a covalent bond, and exhibit a shrinkage rate of 20% or less when formed into a paper shape with a basis weight of 50 g / m2.
Citation Information
Patent Citations
Paper making method
JP1981112599A
Mold-releasing composition
JP1988017958A
Deodorant fiber and its production
JP1997031853A
Binder fibrous material
JP2003166118A
Carboxyl group-containing beaten acrylonitrile fiber, method for producing said fiber, and structure containing said fiber
JP6656608B1